The Effectiveness Of Teaching Speaking Using Chain Pictures For Eight Grade Students Of SMPN 1 Karangrayung In 2015/2016 Academic Year - NUGROHO, EKA CENDANAWATI, Anam Sutopo, S. Pd., M. Hum., Dr (2016)
Eka Cendanawati Nugroho. A 320 120 009. THE EFFECTIVENESS OF TEACHING SPEAKING USING CHAIN PICTURES FOR EIGHT GRADE STUDENTS OF SMP N 1 KARANGRAYUNG IN 2015/2016 ACADEMIC YEAR. Research Paper . Muhammadiyah University of Surakarta. 2016. Education system has many technique that can be used for teaching-learning process. The purpose of this research is to know the effectiveness of english language learning and the implementation in english language learning, also to understand the problems encountered by studens and the solution done by students using chain picture method at SMP N 1 Karangrayung. The type of this research is descriptive-qualitative type , in data obtaining, the researcher uses three data obtaining, those are observation, interview, and documentation. The each meeting the teacher always used a different material. The conclusion of this research is that the researcher can show the result of the research that teaching english language using chain picture can be effective. According to the researcher for four meeting, every meeting session the result obtained shows significant increasing when english learning is done with chain picture method. Keywords : effectiveness, speaking, chain picture, junior high school.